Public Perception of Solid Waste Management in Kuching, Sarawak - Jessica Ranjieng, Wit; Audrey, Liwan; Riccardo, Corrado (2022)
This study examines practices related to waste management in Kuching, Sarawak, and its public perception. A total of 250 answers were collected from Kuching citizens through a survey questionnaire. The Statistical Package for Social Sciences (SPSS) Software was used for data analysis. The results from this study confirm the positive relationship between attitude toward solid waste management and public perception of solid waste management in Kuching. Meanwhile, knowledge regarding proper waste management and public perception was found to be positive as well. Recycling awareness indicates a positive link with practices of solid waste management. Additionally, there is also a positive relationship between behaviour toward solid waste management and practices of solid waste management. In accordance with the results of this study, the recommendations are: centralize solid waste management, place major emphasis on an integrated solid waste management system, while increasing the allocation of funds for existing solid waste management practices, and enforce mandatory source separation.